Price Discovery and Foreign Participation in the Republic of Korea's Government Bond Cash and Futures Markets - Cyn-Young Park; Rogelio Mercado; Jaehun Choi; Hosung Lim (Asian Development Bank (ADB), 2015)
This paper examines the impact of foreign participation in Korean Treasury Bond (KTB) futures and its role in price discovery for KTBs, using daily transactions data from the over-the-counter market for KTBs and from the Korea Exchange for the futures. Our analysis suggests that foreign trading in the KTB futures market leads the price discovery process for the underlying bonds. Empirical results show that foreigners' daily net long positions in the futures market exert significant influence in KTB and KTB futures prices. We also find that it is the unexpected component of foreign investors' net long futures positions that explains a significant share of the pricing effects, suggesting that how foreign trading responds to news carries additional information content.
hdl:11540/3301
Keywords: G10; G13; G14; 330; price discovery; emerging market bonds; foreign participation